1994
DOI: 10.1063/1.467362
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical and quasiclassical calculations for the H+D2→HD+D reaction: Reaction probabilities and differential cross sections

Abstract: A detailed comparison of quasiclassical trajectory (QCT) and quantum mechanical (QM) reaction probabilities and differential cross sections for the H + D 2 -+ HD + D reaction at the collision energies of 0.54 and 1.29 e V has been carried out using the same potential energy surface. The theoretical simulation of the recently published experimental results is also reported. The comparisons made here demonstrate the level of agreement between QCT and QM approaches, as well as between theory and experiment for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Indeed, various quantum results show that forward scattering is exclusively due to partial waves with high total angular momentum J, which corresponds to high impact parameters. 4,9,11 Although the classical dynamics is unable to reproduce quantum effects such as interferences and tunneling and, thus, cannot reproduce certain experimental results accurately, QCT results are nonetheless in surprisingly good agreement with experimental and QM cross sections for this reaction, 2,8,14 which shows that the nuclear dynamics is predominately classical. In particular, we have recently demonstrated that the QCT method can give valuable insight into the motions of the nuclei during a reactive encounter and, thus, elucidate reaction mechanisms.…”
Section: 10supporting
confidence: 62%
“…Indeed, various quantum results show that forward scattering is exclusively due to partial waves with high total angular momentum J, which corresponds to high impact parameters. 4,9,11 Although the classical dynamics is unable to reproduce quantum effects such as interferences and tunneling and, thus, cannot reproduce certain experimental results accurately, QCT results are nonetheless in surprisingly good agreement with experimental and QM cross sections for this reaction, 2,8,14 which shows that the nuclear dynamics is predominately classical. In particular, we have recently demonstrated that the QCT method can give valuable insight into the motions of the nuclei during a reactive encounter and, thus, elucidate reaction mechanisms.…”
Section: 10supporting
confidence: 62%
“…In principle, the QCT calculations already employed at lower collision energies with reasonable success to predict integral 25-34 and differential cross sections 28,30,35,36 should become more accurate. As the collision energy is increased, the effects of zeropoint energy and nonclassical behavior generally become less prominent.…”
Section: Introductionmentioning
confidence: 99%
“…Although QCT cannot accurately reproduce experiments in as much detail as QM, it has been used for a wide number of studies of the hydrogen exchange reaction and has shown surprisingly good agreement with experimental and quantum mechanical cross sections. [14][15][16] However, QCT can nevertheless give valuable insight into the mechanisms leading to reaction. 17 This has been used to investigate short-lived collision complexes ͑in terms of time delay͒ 18,19 and for general investigation of the hydrogen exchange reaction.…”
Section: Introductionmentioning
confidence: 99%